ANALYSIS OF TRANSPORT PHENOMENA ANDIJAN DISTRICT WITH THE FOOT IN THE WAY - M.Abdulakimov; D.Mukimova (Лучшие интеллектуальные исследования, 2024)
Annotation Special problems of road sides and, above all, "the car-drive-way-on foot" through the system is determined. These in turn operate in the environment Today it is considered one of the important issues for the study of this system